The priority of the person political, philosophical, and historical discoveries - Walsh, David 1950- (University of Notre Dame Press, 2020)
"In The Priority of the Person, world-class philosopher David Walsh advances the argument set forth in his highly original philosophic meditation Politics of the Person as the Politics of Being (2015), that "person" is the central category of modern political thought and philosophy. This book is divided into three main parts. Beginning with the political discovery of the inexhaustibility of persons, it then explores the philosophic differentiation of the idea of the "person," and finally traces its historical emergence through art, science, and faith. Walsh argues that, although the roots of the idea of "person" are found in the Greek concept of the mind and in the Christian conception of the soul, this notion is ultimately a distinctly modern achievement, because it is only the modern turn toward interiority that illuminated the unique nature of persons as each being a world unto him or herself. As Walsh shows, it is precisely this feature of persons that makes it possible for us to know and communicate with others, for we can only give and receive one another as persons. In this way alone can we became friends and, in friendship, build community. In showing how the person is modernity's central preoccupation, and in demonstrating how it is only as persons that we can truly give ourselves to others and thus develop real community, David Walsh's The Priority of the Person makes an important contribution to current discussions in both political theory and philosophy. It will also appeal to students and scholars of theology and literature, and any groups interested in the person and personalism"--
Keywords: Geschichte; Politische Anthropologie; Politik; Philosophie; Philosophische Anthropologie; Literatur; Person; Philosophical anthropology; Persons